VOLCANISM OF HOT SPOTS ON THE RÉUNION AS THE EXAMPLE - Dragan Radovanović; Danica Srećković-Batoćanin; Aleksandar Valjarević (Zbornik Radova: Geografski institut "Jovan Cvijić", 2016)
Réunion (French: La Réunion, formerly: Īle Bourbon) is beside the Mauritius the largest and the youngest island on the Mascarene Plateau in the Indian Ocean. The island is of volcanic origin, formed through volcanic activity initiated by deeply settled “hot spot” inside the Earth’s mantle. It was formed within the last 2 million years from lava effusions whose volume is up to now nearly 75,000 km3. Only 3% of its volume is emergent and the total height from the sea floor is 6,500 m. The island is about 40 km in width with about 800,000 inhabitants. The capital city is St Denis. The nature of the island is impressive: active volcano, mountains above 3,000 m in height and deep canyon, frequently exceeding 2,000 m in depth. Since 2010, about 40% of its area is announced a National park and a UNESCO World Heritage site.